FENOMENOLOGI PENGALAMAN BELAJAR SISWA YANG MENGALAMI KECEMASAN MATEMATIKA - Aries Nur Shandy; Fahmi Rizqi Nashrullah; Yosi Pebriana; Duta Prima Manunggal (LPPM Institut Ahmad Dahlan Probolinggo, 2026)
This research aims to explore and interpret the life experiences of students who experience mathematical anxiety through a phenomenological approach. The study used a qualitative descriptive phenomenological design involving 100 junior high school students in Cirebon. Participants were selected purposively based on initial indications of math anxiety, teachers' recommendations, and willingness to reflect on learning experiences. An in-depth semi-structured interview was conducted with 8 students until data saturation was achieved, and supported by learning observation and documentation. Data analysis is carried out through epoche stages (bracketing), horizontalization, identification of significant statements, formulation of meaning units, grouping of themes, and preparation of textural and structural descriptions to find the essence of the phenomenon. The results of the study show that mathematical anxiety is a complex and multidimensional experience formed through the interaction of emotional, cognitive, and social aspects in the learning environment. Students express intense emotional emotions such as fear, nervousness, and physical symptoms especially in evaluative situations. Cognitively, anxiety interferes with concentration and inhibits access to the knowledge that has been mastered, thereby lowering confidence and academic performance. Negative perceptions of math and unsupportive classroom dynamics also reinforce anxiety. The essence of math anxiety is not solely in cognitive difficulties, but in the subjective meanings that build students towards their learning experiences. These findings emphasize the importance of learning strategies that are humane and support students' psychological states.